Analysis of skin health management through telemedicine and mobile health in dermatology in the post-COVID era - Gençoğlu, Şule (The European Research Journal, 2025)
Mobile health has made significant strides in the field of tele-dermatology (TD) following the developments post the COVID-19 pandemic. The application of telemedicine and mobile health to dermatology holds the potential to enhance the quality of healthcare for citizens and streamline workflows in the healthcare domain, hence this subject is of great importance. This research encompasses the last three years. A comprehensive overview examining the opportunities, perspectives, and encountered challenges regarding the integration of TD with mHealth has been provided. The narrative review methodology is based on (I) conducting research via PubMed and Scopus, and (II) conducting compliance assessment using the proposed parameters. The outcome of the research indicates rapid progress in the integration of TD with mobile health during the COVID-19 pandemic. This integration has facilitated the monitoring of dermatological issues and allowed for remote specialist visits, thereby reducing face-to-face interactions. Artificial intelligence and mobile applications have empowered citizens to take a more active role in their own healthcare, which is distinct from other imaging areas where information exchange is limited only to professionals. Opportunities that TD can offer in the field of mobile health include enhancing service quality, increasing the efficiency of healthcare processes, reducing costs, and providing more accessible care. This is applicable not only to conditions like acne, vitiligo, psoriasis, and skin cancers but also to other conditions. Integration with artificial intelligence and augmented reality (AR), along with the use of wearable sensors, are expected as future developments. However, the integration of TD with mobile health brings along issues and challenges related to regulation, ethics, cybersecurity, data privacy, and device management. These issues, along with the involvement of citizens in the process, should be addressed by scientists and policymakers.